Hubungan Kecerdasan Emosi Dengan Psychological Well-Being Pada Mahasiswa Universitas Negeri Padang - Maia Welia Dinda; Assri Fitrida Putri; Ilmenia Zulianty; Hanisa Azura; Ulfa Dwina; Geni Novella; Syintia Rahma Dinda (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
The study period is an important phase in a person's educational journey at college or university level. 3rd and 5th semester students often experience higher pressure due to increasingly complex and demanding coursework. This study aims to investigate the correlation between emotional intelligence and Psychological Well-Being among Padang State University students. This research method is quantitative correlation using Product moment correlation analysis. The results show a strong and significant positive correlation (Pearson correlation coefficient = 0.625) between emotional intelligence and Psychological Well-Being. With a significance value of <0.01. Findings showed that individuals with higher psychological well-being tended to have positive emotions and pleasant feelings, whereas those with lower psychological well-being tended to have negative emotions and less pleasant feelings.